A synthesis of new 7-amino-substituted 4-aminopyrazolo[1,5-a][1,3,5]triazines via a selective three-component triazine ring annulation - Lim, Felicia Phei Lin; Luna, Giuseppe; Tan, Khai Ching; Tiekink, Edward R. T. *; Dolzhenko, Anton V (Elsevier, 2019)
3-Amino-substituted 5-aminopyrazoles were found to be suitable substrates for the synthesis of new 4-aminopyrazolo[1,5-a][1,3,5]triazines (5-aza-9-deaza-adenines) when used in the one-pot, three-component reaction with cyanamide and triethyl orthoformate under microwave irradiation. The reaction proceeded selectively and its scope was demonstrated by the preparation of a library of 4-aminopyrazolo[1,5-a][1,3,5]triazines. Some structural aspects of the prepared compounds were investigated using dynamic NMR spectroscopy and X-ray crystallography. The operational simplicity, short reaction time, and good reproducibility are attractive features of the developed robust and practical approach for the synthesis of 7-amino-substituted 4-aminopyrazolo[1,5-a][1,3,5]triazines.